Smallholder farmers' perceptions of climate variability and its risks across agroecological zones in the Ayehu watershed, Upper Blue Nile Basin, Ethiopia - Abebe Biresaw Bitew; Amare Sewnet Minale (Environmental and Sustainability Indicators)
Understanding farmers' perceptions of climate variability is crucial for developing adaptation strategies that reflect farmers' experiences and observations. This study investigates perceptions of climate variability and associated risks among smallholder farmers in the Ayehu watershed, Upper Blue Nile Basin, Ethiopia. The study surveyed a sample of 338 participants selected randomly. We employed the Mann-Kendall test and Sen's slope estimator to examine the actual trends and magnitude of temperature and rainfall. Further, this study used the Severity Index (SI) and Standardized Climate-Related Risk Perception Index (SCRRPI) to assess farmers' perceived features of climate variability and associated risks. We used a binary logit model to identify the determinant factors influencing farmers' perceptions of climate variability. Findings showed a non-significant decline in annual rainfall (0.96 mm/year) but a significant increase in Kiremt season rainfall (5.4 mm/year). The minimum temperature rose by 0.03 °C per year, while the maximum increased by 0.02 °C annually. In the lowland area, 86% of farmers noted a rise in temperature trends, while 79% indicated a decrease in rainfall. ANOVA results indicated significant differences in climate perception across zones (P < 0.01), with farmers' views aligning with actual climate data trends. SCRRPI identified crop pests, declining yields, drought, and water scarcity as perceived climate risks across agroecological zones. The binary logistic regression revealed that climate information, farming experience, and extension services significantly shaped farmers' perceptions. The study concludes that farm households' perceptions of temperature and rainfall variability vary across agroecological zones. Policymakers should consider these differences when developing climate adaptation strategies.